1999
DOI: 10.1097/00007890-199904270-00019
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation in Recipients Over the Age of 60

Abstract: Although the overall outcomes of transplantation in older recipients remain reasonable, the inferior outcomes with older donor kidneys call into question proposals to utilize older donor kidneys preferentially in older recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
43
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(54 citation statements)
references
References 11 publications
9
43
0
2
Order By: Relevance
“…Contradicting this idea, Basar et al 20 clearly showed inferior outcomes when elderly donor grafts were used in older recipients, seeming that there is an added phenomenon of harmful factors. Based on our results, we recommend an old-for-old program, 13 where ABO-compatible organs from elderly donors with a negative cross-match, are locally allocated to old recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Contradicting this idea, Basar et al 20 clearly showed inferior outcomes when elderly donor grafts were used in older recipients, seeming that there is an added phenomenon of harmful factors. Based on our results, we recommend an old-for-old program, 13 where ABO-compatible organs from elderly donors with a negative cross-match, are locally allocated to old recipients.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is controversy regarding the outcomes with older kidneys. 7,15,16 Donor age was significantly higher in our older recipients. We analyzed the outcome of our elderly patients according to donor's age and failed to observe a significant difference in actuarial patient and graft survivals when comparing older recipients of kidneys from an aging donor.…”
Section: Discussionmentioning
confidence: 69%
“…The aging causes a series of morphological and physiological changes to the kidneys leading to an increased glomerular, vascular, and tubular senescence [31,32]. Such morphological changes can result in significant functional changes including a decrease in renal blood flow and glomerular filtration rate, leading to an overall deterioration in renal function [6].…”
Section: The Marginal Kidneymentioning
confidence: 99%